Association between Body Roundness Index and Depression Among Middle-aged and Older Adults in Chinese Communities: An Empirical Analysis Based on CHARLS Data - Wenfei Yang; Liping Chen; Liling Tong; Wenchang He; Hua Lin (PLoS ONE, 2025)
Background The relationship between depression and obesity has been confirmed by multiple studies. Compared to conventional measurement indicators such as body mass index or waist circumference, the body roundness index (BRI) demonstrates higher accuracy in assessing body fat content, especially visceral adiposity. Nevertheless, despite the advantages of BRI in measuring fat, the specific link between BRI and depression remains unclear. This study aims to clarify the potential correlation using data from the China Health and Retirement Longitudinal Study (CHARLS). Methods This study used CHARLS data from 2015 and 2020. We screened and included 7,258 middle-aged and older adults without depressive symptoms at baseline. We explored the connection between BRI and depression risk through logistic regression analyses, restricted cubic spline analyses, subgroup analyses, and interaction tests Results After adjusting for covariates, a positive correlation was observed between BRI and depression risk. Specifically, a one-unit increase in BRI led to a 14% increase in depression risk (OR =  1.14, 95% CI: 1.09-1.20, P <  0.001). Conclusion BRI is linked to a higher risk of depression in middle-aged and older adults in China and can be used as a simple indicator to predict depression.